Analisis Standar Penilaian Pendidikan Di Indonesia (Permendidkbud No 21 Tahun 2022) - Noptario Noptario; Siti Aisyah; Muhammad Najib; Shaleh Shaleh (Peneliti.net, 2023)
The purpose of this study was to find out the standards for evaluating education in Indonesia based on Permendikbud No. 21 of 2022. The research method used was literature study. The type of data used is data generated from literature studies, namely data related to Permendikbud No. 21 of 2022. Using a descriptive analysis method. Permendikbud No.21 of 2022 contains student assessment standards and aspects that are developed in the learning process. Assessment of student learning outcomes is carried out in accordance with the objectives of the assessment in a fair, objective and educative manner. In carrying out the assessment the teacher must first determine the assessment criteria before making a decision and must be adjusted to the conditions that exist in the class. Structured and systematic assessment procedures consist of formulation of assessment objectives, selection and development of assessment instruments, processing of assessment results and reporting of assessment results. The assessment is carried out by educators taking into account the characteristics of the needs of students and based on an assessment plan that is in accordance with the lesson plan.